All fours : a novel - July, Miranda, 1974- (Riverhead Books, 2024)
"A semi-famous artist announces her plan to drive cross-country, from LA to NY. Twenty minutes after leaving her husband and child at home, she spontaneously exits the freeway, beds down in a nondescript motel, and immerses herself in a temporary reinvention that turns out to be the start of an entirely different journey"--